2002
DOI: 10.1034/j.1600-051x.2002.290905.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic polymorphisms at the interleukin‐10 loci in aggressive and chronic periodontitis

Abstract: We conclude that the investigated polymorphisms are not associated with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
4
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 40 publications
3
60
4
4
Order By: Relevance
“…Racial and ethnic characteristics play a role on these results. Gonzales et al 4 searched gene polymorphism in IL-10(-592) loci in AgP and CP Caucasian patients. Contrary to our results, they found no association between IL-10 AA genotype and AgP; similar results were found by Hu et al 23 in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Racial and ethnic characteristics play a role on these results. Gonzales et al 4 searched gene polymorphism in IL-10(-592) loci in AgP and CP Caucasian patients. Contrary to our results, they found no association between IL-10 AA genotype and AgP; similar results were found by Hu et al 23 in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…4,21,24 The IL-10 gene polymorphism at position -597 C to A wasnot associated with the susceptibility to CP or AgP. 4 Considering the key roles of pro-inflammatory and anti-inflammatory cytokines in periodontal disease, it was questioned whether genetic variations affecting transcription or function of these cytokines contribute to the development of GAgP. Also, few studies have investigated the potential association of carrying a gene variant with the clinical response to periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of an association between IL-10 gene polymorphisms and clinical manifestations of chronic and aggressive periodontitis is controversial. Some of the studies failed to find any evidence of association (4,19,20) and others revealed a possible association between this polymorphism and periodontitis (17,(21)(22)(23)(24). Considering the multifactorial nature of a periodontal disease, little is known among the complex interaction of the polymorphisms in the promoter regions of IL-6 (-174), IL-10 (-597) and NF-κB1 (-94ins/del) genes and clinical parameters of periodontitis.…”
Section: Introductionmentioning
confidence: 99%